The Impacts of Ethical Sales Behaviour on Customer Loyalty in the Life Insurance Industry in Pakistan - Dildar Khan Jadoon; Awais Qasim; Dr. Asia Bibi (HM Journals, 2024)
The life insurance industry in Pakistan is highly competitive, with customer loyalty playing a crucial role in long-term success. Ethical sales behaviour emerges as a key differentiator, potentially fostering trust and driving positive customer experiences. This research investigates the relationship among ethical sales behaviour, customer trust in company and trust in sales agent, which directly affect customer loyalty in the life insurance industry. The quantitative survey targets customers of five major life insurance companies, ensuring a representative sample across diverse demographics. The questionnaires were sent to all companies customer on a random basis. The questionnaires are distributed with the help of office employee of the companies.The finding of the study shows that there is a direct and positive relation between sales agent ethical sales behaviour and customer loyalty. Furthermore, the trust of the customer in the sales agent and trust of the customer in a company has direct positive mutual relation and customer trust both affect customer loyalty. By demonstrating the tangible benefits of ethical sales behaviour, the study can encourage companies to implement and prioritize ethical practices. The identified key drivers of customer loyalty can guide training programs and performance evaluations for insurance agents, ultimately fostering a culture of ethical conduct within the industry.